Comparative leaf morphology and anatomy on ten taxa of Calycanthaceae Lindl. (Laurales) (Our Nature, 2021)
The comparative leaf morphology and anatomy of ten species of family Calycanthaceae have been studied. Leaf anatomy is very comparable to each other in cell shape and their arrangement. Collected leaves were preserved in FAA and alcohol series were applied for LM and SEM. The layer of epidermis is two in Idiospermum and one in rest of other genera. The structure of vascular bundle is V-shape in Sinocalycanthus and Calycanthus whereas U-shape in Idiospermum and Chimonanthus. The density of trichome is higher in Calycanthus than other genera. The presence of trichome, stomata, epidermal layer, density of trichome and stomata, and leaf surface are represented the distinction among the genera. The adaxial surface of Idiospermum and Sinocalycanthus are smooth whereas of Calycanthus and Chimonanthus are rough. The crystals are present in Calycanthus, Sinocalycanthus and Chimonanthus whereas absent in Idiospermum. The shape of the vascular bundle, density of trichome, epidermal layer, and crystals play important role in the phylogenetic relationship of Calycanthaceae.